2013
DOI: 10.1037/a0031847
|View full text |Cite
|
Sign up to set email alerts
|

Comparison promotes learning and transfer of relational categories.

Abstract: We investigated the effect of co-presenting training items during supervised classification learning of novel relational categories. Strong evidence exists that comparison induces a structural alignment process that renders common relational structure more salient. We hypothesized that comparisons between exemplars would facilitate learning and transfer of categories that cohere around a common relational property. The effect of comparison was investigated using learning trials that elicited a separate classif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
61
1
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 46 publications
(72 citation statements)
references
References 57 publications
5
61
1
2
Order By: Relevance
“…Our finding that analogical comparison can support the abstraction of such causal structures is consistent with past work showing that comparing examples supports forming relational categories (Christie & Gentner, 2010;Gentner et al, 2011;Jung & Hummel, 2011;Kotovsky & Gentner, 1996;Kurtz et al, 2013;Tomlinson & Love, 2010). Further, our finding that alignment was most beneficial when exemplar relational representations were accurately represented accords with those of Doumas and Hummel (2013) who found that alignment aids learning category-defining higher-order relations (i.e., relations among relations) only when the lower-order relations are properly represented.…”
Section: Category Learning and Representationsupporting
confidence: 93%
See 1 more Smart Citation
“…Our finding that analogical comparison can support the abstraction of such causal structures is consistent with past work showing that comparing examples supports forming relational categories (Christie & Gentner, 2010;Gentner et al, 2011;Jung & Hummel, 2011;Kotovsky & Gentner, 1996;Kurtz et al, 2013;Tomlinson & Love, 2010). Further, our finding that alignment was most beneficial when exemplar relational representations were accurately represented accords with those of Doumas and Hummel (2013) who found that alignment aids learning category-defining higher-order relations (i.e., relations among relations) only when the lower-order relations are properly represented.…”
Section: Category Learning and Representationsupporting
confidence: 93%
“…There is considerable prior evidence consistent with the idea that analogical comparison highlights common relations through a process of structural alignment (Falkenhainer, Forbus, & Gentner, 1989;Gentner & Markman, 1997), and that such an alignment permits learners to notice the common structure, which can then be applied more broadly. The idea that analogical comparison promotes transfer from specific learning contexts has received support from research with adults (Gick & Holyoak, 1983;Kurtz, Boukrina, & Gentner, 2013) and children (Christie & Gentner, 2010;Gentner, Anggoro, & Klibanoff, 2011) and by studies in educational contexts (Gentner, Loewenstein, & Thompson, 2003;Klahr & Chen, 2011;Rittle-Johnson & Star, 2009). …”
Section: Introductionmentioning
confidence: 97%
“…Kurtz, Boukrina, & Gentner, 2013). In this case, common relational structure is defined by spatial relations, and an alignable difference is one that occupies the same role in the spatial structure of the two items compared.…”
Section: Comparison and Difference Detectionmentioning
confidence: 99%
“…Only instances compared to one another to derive a general schema for a class of instances facilitated forward transfer, compared to situations where instances were offered but no comparison was provided [Gick, Holyoak, 1980;Kurtz, Boukrina, Gentner, 2013]. It also turned out that a simple instruction to solving method is not enough, and neither are simple example-based illustrations.…”
Section: Conducive Learningmentioning
confidence: 99%